Interspecific Hybridization Is an Important Driving Force for Origin and Diversification of Asian Cultivated Rice Oryza sativa L. - Zhou, Jiawu; Yang, Ying; Lv, Yonggang; Pu, Qiuhong; Li, Jing; Zhang, Yu; Deng, Xianneng; Wang, Min; Wang, Jie; Tao, Dayun (Frontiers in Plant Science, 2022)
As one of the most important crops, Asian cultivated rice has evolved in a complex group including several subgroups adapting various eco-climate-systems in the globe. Here, we pictured a comprehensive view about its original domestication, divergences, and the origin of different subgroups by integrating agriculture, archaeology, genetics, nuclear and cytoplasm genome results. Then, it was highlighted that interspecific hybridization-introgression has being played important roles in improving genetic diversity and adaptation of O. sativa during its evolution process. Natural hybridization-introgression led to the origin of indica, aus, and basmatic subgroups, which adapted changing cultivated environments, and produced feral weedy rice coexisting and competing with cultivars under production management. Artificial inter-specific hybridization-introgression gained several breakthroughs in rice breeding, such as developing three-line hybrid rice, new rice for Africa (NERICA), and some important pest resistance genes in rice genetic improvement, contributed to stable increase of rice production to meet the expanding human population. We proposed series to exploit the virtues of hybridization-introgression in genetic improvement of Asian cultivated rice. But some key issues such as reproductive barriers especially hybrid sterility should be investigated further, which are conducive to gene exchange between cultivated rice and its relatives, even is beneficial to exploit inter-specific hybrid vigor. New technologies help introduce favorable genes from distant wild species to Asian cultivated rice, such as transgenic, and genome editing systems. Rising introgression lines in a wider range with multi-donor benefits allele mining, understanding genetic network of rice growth and development, yield formation and environmental adaptation. Then, integration of new tools and interspecific hybridization can be future direction to develop more usable breeding populations which can make Asian cultivated rice more resilience to the changing climate and world.